Waterproof and anti-aging photovoltaic cable and preparation process thereof
By blending LDPE, LLDPE, EVA and inorganic fillers, and using ultraviolet crosslinking method, a photovoltaic cable insulation layer with high water resistance and water resistance performance is formed, which solves the problem of water branches of photovoltaic cables in humid environments and extends the cable lifespan and improved performance.
Patent Information
- Application Number
- CN202411096392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-08-12
AI Technical Summary
Photovoltaic cables are prone to water branches in humid environments, resulting in a decrease in electrical and mechanical properties of the insulating layer, seriously affecting the service life of the cable and the reliability of the power supply.
Blends of LDPE, LLDPE, EVA, inorganic fillers, photoinitiators and crosslinking agents, and insulating layers are formed through extrusion and irradiation processes, combined with ultraviolet crosslinking method to generate crosslinked polyethylene to prevent moisture penetration and electric field force. It can enhance the water resistance and water resistance of the insulating layer.
It significantly improves the water resistance and water resistance of the insulating layer of photovoltaic cables, extends the service life of the cable, and improves the strength and toughness of the insulating layer, reducing conductivity and breakdown field strength.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cables, in particular to a waterproof and anti-aging photovoltaic cable and a preparation process thereof. Background Art
[0002] Nowadays, people are increasingly aware of environmentally friendly energy, and new energy sources such as wind energy and solar energy are constantly being developed. As a clean, green, and renewable energy source, photovoltaic power generation uses the photovoltaic effect of the semiconductor interface to directly convert abundant solar radiation energy into electrical energy. In order to meet the complex operating conditions of photovoltaic power stations, the performance of photovoltaic power generation cables needs to be improved to adapt to the actual application environment. PE (polyethylene) has excellent mechanical, physical, and electrical properties and good processing characteristics. It is processed from a linear structure into a three-dimensional mesh structure by cross-linking, and thermoplasticity is converted into thermosetting. The mechanical properties, thermal stability, and environmental stress cracking resistance of the prepared XLPE (cross-linked polyethylene) are further improved, and the thermal stability and heat resistance of the cable are also improved; but this is not enough to meet the stringent requirements of the cable on the electrical properties of the insulation material.
[0003] In a humid environment, the insulation layer of the cable will gradually absorb the surrounding moisture. Under the combined action of the electric field and water, dendrites will appear inside the polymer dielectric of the cable insulation layer, which is called water dendrites. Its existence will seriously affect the electrical and mechanical properties of the cable insulation layer, and will cause the generation of electrical dendrites and insulation breakdown failures under certain conditions, making the insulation layer fail, greatly shortening the service life of the cable, and seriously affecting the reliability of power supply. Studies have shown that EVA (ethylene-vinyl acetate copolymer) can inhibit the growth of water dendrites in XLPE, and its mixture has good anti-aging properties. The attraction of polar polymer EVA to water is greater than the cohesive force of water molecules. Water molecules are adsorbed on the surface of the polar groups of EVA, and it is difficult for water to aggregate in the polymer, which reduces the condensation of water in the amorphous area of XLPE, weakens the expansion and contraction deformation of water under the alternating electric field, and alleviates the stress damage formed by the molecular chain, thereby showing a good water dendrite inhibition effect.
[0004] However, under long-term humid and water-immersion conditions, the adhesion between the filler and the matrix resin decreases, the molecular chain hydrolyzes, the entanglement between the molecular chains weakens, the EVA absorbs water and swells, the free volume increases, and the mechanical properties of the insulation layer decrease; part of the filler is separated from the matrix resin, resulting in a continuous decrease in the volume resistivity of the cable. Therefore, we propose a waterproof and anti-aging photovoltaic cable and its preparation process. Summary of the invention
[0005] The object of the present invention is to provide a waterproof and anti-aging photovoltaic cable and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: LDPE, LLDPE, EVA, inorganic filler, photoinitiator, crosslinking agent and additives are blended and kneaded to obtain an insulating material; The insulating material is extruded to cover the conductor; the conductor is heated and irradiated to form an insulating layer; the sheath material is extruded to cover the insulating layer to form a sheath layer, thereby obtaining a photovoltaic cable.
[0007] Furthermore, the photovoltaic cable includes the following structures from the inside to the outside: a conductor, an insulation layer and a sheath layer.
[0008] Furthermore, the mixing process conditions are: temperature 145-160° C., rotation speed 40-60 rpm, and time 20-30 min.
[0009] Furthermore, the extrusion process conditions are: extrusion temperature 145-170° C., monomer line speed 2.0-3.0 m / min.
[0010] Furthermore, the heating process conditions are: temperature 155-170° C., time 44-76 s.
[0011] Furthermore, the irradiation process conditions are: UV lamp power 1.0W×12 groups, duration 76 to 136s.
[0012] In the above technical scheme, the cross-linking methods of PE include irradiation, peroxide, silane, etc. Among them, high-energy radiation cross-linking has the problem of low penetration depth, and can only produce low-voltage small-interface wires and cables. Silane cross-linking will increase the water content in the insulation layer, resulting in greater polarity, which is not suitable for the production of medium and high voltage power cables. Therefore, at present, the peroxide cross-linking method is mostly used to produce medium and high voltage XLPE insulated power cables; but the by-products methane, cumyl alcohol, acetophenone, α-methylstyrene and water produced during the cross-linking reaction will have a negative impact on the dielectric properties of the insulation layer; and it will also be limited in the selection of PE resin and the single continuous processing time. The ultraviolet light cross-linking method has the characteristics of photon effect and non-thermal sensitivity of materials, and has the advantages of fast cross-linking speed, long continuous processing time, multiple selectivity of insulating extrusion resins, low investment cost, energy saving and emission reduction.
[0013] Furthermore, the insulating material includes the following components by mass: 50 to 90 parts of LDPE (low-density polyethylene), 10 to 50 parts of LLDPE (linear low-density polyethylene), 6 to 12 parts of EVA (ethylene-vinyl acetate copolymer), 1 to 3 parts of photoinitiator, 1 to 3 parts of cross-linking agent, 0.5 to 3.0 parts of inorganic filler, and 0.2 to 0.5 parts of auxiliary agent.
[0014] In the above technical scheme, compared with LDPE (low-density polyethylene) and HDPE (high-density polyethylene), LLDPE (linear low-density polyethylene) has a dense short-chain branched molecular structure, which can promote entanglement between lamellae. In the amorphous phase of LLDPE, water requires more energy and time to destroy these entangled molecular chains, and the entangled molecular chains can inhibit the slippage of lamellae under the extrusion force of water to a certain extent, thereby weakening the destructive effect caused by electro-induced stress and inhibiting the growth of water dendrites, making LLDPE have stronger resistance to water dendrite aging. However, the extrusion processing performance of LLDPE is poor, which will affect the comprehensive performance of the extrudate. Therefore, a mixture of LDPE and LLDPE is taken as the base resin of XLPE.
[0015] Furthermore, the photoinitiator is one of benzophenone and 4-hydroxybenzophenone laurate.
[0016] Furthermore, the crosslinking agent is a mixture of one or more of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, diallyl phthalate, pentaerythritol triallyl ether, and pentaerythritol tetraallyl ether.
[0017] In the above technical scheme, the irradiation process enables the photoinitiator to play a role, crosslinking and combining polyethylene with the crosslinking agent to generate XLPE (crosslinked polyethylene). The three-dimensional network structure formed by crosslinking can effectively prevent water from penetrating into the interior of XLPE under the action of electric field force, narrowing the water dendrite channel, enhancing the barrier effect, and improving the water resistance and anti-water dendrite performance of XLPE. The crosslinked bonds formed make the β relaxation of XLPE stronger, which can buffer the impact of water on the amorphous phase of XLPE under the action of electric field force and reduce the growth rate of water dendrites; the entanglement behavior of the molecular chain in the amorphous region is strengthened, and the difficulty of slip and destruction between the lamellae under the action of electro-induced stress increases, thereby improving the ability of the insulating layer to inhibit water dendrites. Select a macromolecular photoinitiator, which has better thermal stability, is not easy to volatilize when heated, and has better efficiency of photocrosslinking reaction.
[0018] Furthermore, the inorganic filler is a mixture of one or more of silica, montmorillonite and alumina.
[0019] In the above technical solution, adding an appropriate amount of inorganic filler can promote the heterogeneous nucleation of XLPE, improve the crystal morphology of XLPE, reduce the amorphous phase area, inhibit the penetration of water, and enhance the water-resistant dendrite ability of XLPE.
[0020] Furthermore, the auxiliary agent is a mixture of one or more of antioxidant 1010 , antioxidant 300 , and antioxidant 1035 .
[0021] Furthermore, EVA is modified, and the specific process is as follows: Mix EVA and toluene, heat to 60-70°C, and stir to dissolve; slowly add sodium hydroxide / methanol solution within 10 minutes, and stir to react for 100-150 minutes; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; The alcoholysis product of EVA and toluene are mixed, heated to 60-70°C under the protection of nitrogen atmosphere, and stirred for 30-60 minutes; 2,5,5-trimethylheptanoyl chloride, 3,5,5-trimethylhexanoyl chloride and acryloyl chloride are slowly added, and stirred for reaction for 120-150 minutes; an acid binding agent is added, and the reaction is carried out for 90-120 minutes; the mixture is cooled, precipitated with ethanol, filtered, the precipitate is washed, and dried to obtain alkenyl EVA; The alkenyl EVA and toluene are mixed, a dithiol compound and a photoinitiator are added, the mixture is stirred and irradiated with an ultraviolet lamp for 2 to 4 hours; an alkenyl carbazole compound is added, and the irradiation is continued for 8 to 12 hours; the mixture is washed and dried to obtain the modified EVA.
[0022] Further, the ratio of EVA, toluene, and sodium hydroxide / methanol solution is (5-6) g:100 mL:50 mL; The concentration of the sodium hydroxide / methanol solution was 5 wt %.
[0023] Further, the ratio of EVA alcoholysis product and toluene is (1-2) g:100 mL; The acid binding agent is triethanolamine; The olefin EVA comprises the following components by mass: 100 parts of EVA alcoholysis product, 1 to 4 parts of 3,5,5-trimethylhexanoyl chloride (isononanoyl chloride CAS No. 36727-29-4), 0 to 3 parts of 2,5,5-trimethylheptanoyl chloride (neodecanoyl chloride CAS No. 40292-82-8), 4.5 to 6.0 parts of acryloyl chloride, and 12 to 13 parts of acid-binding agent triethanolamine.
[0024] Further, the ratio of alkenyl EVA to toluene is 10 g / 100 mL; The dithiol compound is one of alkyl dithiol, 1,4-benzenedithiol, and hexa(ethylene glycol)dithiol; The modified EVA comprises the following components by mass: 100 parts of alkenyl EVA, 10 to 22 parts of alkenyl carbazole compounds, 5.6 to 22.1 parts of dithiol compounds, and 2.4 to 11.0 parts of photoinitiators; The photoinitiator is dimethyl benzoate.
[0025] Further, the alkenyl carbazole compound is prepared by the following process: Mix 2-hydroxycarbazole and triethylamine in dichloromethane, slowly add 5-norbornene-2-yl chloride at 0-8°C, and add it over 20 minutes; restore the temperature to 20-30°C, react for 90-120 minutes; wash, stand for stratification, take the lower layer of liquid, and dry to obtain a polymerized monomer; Under the protection of nitrogen atmosphere, the polymerization monomer and the annular catalyst are mixed in dichloromethane, the temperature is raised to 50-60° C., and the reaction is carried out for 96-100 hours; the mixture is cooled to -20° C. and precipitated with cold methanol to obtain an alkenyl carbazole compound.
[0026] Further, the molar ratio of 2-hydroxycarbazole, 5-norbornene-2-yl chloride, and triethylamine is 1:(1.0-1.1):(1.0-1.1); The ratio of 2-hydroxycarbazole to dichloromethane is 3 g / 100 mL.
[0027] Further, the amount of the annular catalyst is 0.20 to 0.25% of the mass of the polymerized monomer; The ratio of polymerization monomer to dichloromethane is 30 g / 100 mL; The ring catalyst is a cycloalkylruthenium catalyst, which is prepared by referring to 6cyc in the literature "Boydston AJ, Xia Y, Kornfield JA, et al. Cyclic ruthenium-alkylidene catalysts for ringexpansion metathesispolymerization [J]. Journal of the American Chemical Society, 2008, 130(38):12775-12782".
[0028] In the above technical scheme, the alcoholysis product of EVA is processed by using 3,5,5-trimethylhexanoyl chloride, 2,5,5-trimethylheptanoyl chloride and acryloyl chloride to obtain olefinic EVA. As tertiary carbonates, isononanoic acid ester and neodecanoic acid ester have side chains, which have higher hydrolysis stability while maintaining the hydrophilicity of the ester group, and can effectively improve the water resistance of the insulating layer; the water channel barrier effect is increased, which can effectively prevent the penetration of water, and the slippage of water under the extrusion force is reduced, which improves the water resistance of the insulating layer. The introduction of hard segment isononanoic acid ester and soft segment neodecanoic acid ester in EVA can also synergistically improve the rigidity and toughness of the EVA molecular chain.
[0029] In the preparation of phenone-based acid chloride compounds, 2-hydroxycarbazole and 5-norbornene-2-acid chloride react to form a norbornene acyloxycarbazole compound through nucleophilic addition between the acid chloride and the hydroxyl group, which is recorded as a polymerized monomer. The polymerized monomer undergoes metathesis polymerization under the action of a cyclization catalyst to form a cyclic polymer with strong toughness, which is recorded as an alkenyl carbazole compound. When it is introduced into the structure of the insulation layer, it forms a mechanical interlocking after interlacing with the linear polymer (LDPE, LLDPE, EVA) by UV crosslinking, which can delay the relaxation of the molecular chain and slow down the diffusion of water; and it can absorb the energy of the initiation and growth of microcracks in XLPE to a certain extent, inhibit the initiation and growth of water trees, thereby effectively improving the waterproof tree resistance and anti-aging ability of the prepared insulation layer. In addition, the π electron system in the carbazole structure helps to capture and inhibit the movement of charges of the same polarity, reduce charge migration, improve the insulation strength of the insulation layer, and increase its breakdown field strength; it can inhibit the initiation and further growth of water trees, and effectively extend the service life of the cable.
[0030] Through dithiol compounds, thiol-ene click reaction is utilized to crosslink alkenyl EVA with alkenyl carbazole compounds to obtain modified EVA, so that the modified EVA and the insulating layer made thereof have good strength, toughness, waterproofness, water resistance and aging resistance.
[0031] Furthermore, the inorganic filler is modified, and the specific process is as follows: Mix the crosslinking agent and tetrahydrofuran, adjust the system temperature to 0-8°C under the protection of nitrogen atmosphere, add mercaptosiloxane and triethylamine, stir and return to room temperature, keep the temperature for 24-27 hours, and distill under reduced pressure to obtain allylsiloxane; The inorganic filler is placed in an ethanol solution and ultrasonically dispersed for 20 to 30 minutes, the pH of the system is adjusted to 3.6 to 4.2 using hydrochloric acid, allyl siloxane is added, the temperature is raised to 70 to 80° C., and the reaction is stirred for 8 to 12 hours; washing, suction filtering, and drying are performed to obtain a modified filler.
[0032] Further, the molar ratio of the crosslinking agent, mercaptosiloxane, and triethylamine is 1:1:(1.8-2.5); The mercaptosiloxane is one of γ-mercaptopropyltrimethoxysilane and 11-mercaptoundecyltrimethoxysilane; The ratio of cross-linking agent to tetrahydrofuran was 5 g / 10 mL.
[0033] Further, the allylsiloxane is 10 to 60 wt% of the inorganic filler; The ratio of inorganic filler to ethanol solution is 10 g / 100 mL; The concentration of the ethanol solution is 60-75v%.
[0034] In the above technical scheme, the modified inorganic filler can serve as a physical crosslinking point in XLPE, and form a crosslinking bond with PE and a crosslinking agent during the irradiation process, thereby increasing the crosslinking density of the system and effectively improving the strength and toughness of the insulating layer. The prepared modified filler has a strong interface interaction with XLPE, which can effectively prevent the inorganic filler from being separated from the constraints of the XLPE matrix, improve the water resistance of the insulating layer, and improve its water aging resistance. The large specific surface area of the inorganic filler and the interface interaction between it and XLPE enhance the binding effect of the insulating layer on the carriers, inhibit the migration of the carriers, shorten the free path of the electrons, reduce the conductivity of the insulating layer, and increase the breakdown field strength; the increased binding of the molecular chain inhibits the penetration and diffusion of water in the insulating layer, further improving the water dendrite resistance of the insulating layer.
[0035] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a waterproof and anti-aging photovoltaic cable and a preparation process thereof, wherein olefinic EVA is prepared by nucleophilic addition of 3,5,5-trimethylhexanoyl chloride, 2,5,5-trimethylheptanoyl chloride and an alcoholysis product of EVA. Tertiary carbonate isononanoate and neodecanoate have side chains, which make them have higher hydrolysis stability and effectively improve the water resistance of the insulating layer; and the water channel barrier effect is increased, which can prevent the penetration of water, reduce the slippage of water under the extrusion force, and improve the water resistance of the insulating layer. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] In the following specific implementations, LDPE: DJ210, from Shanghao Jinshan Petrochemical Company; LLDPE: DFDA-7042, from Qilu Petrochemical Company; EVA: EVA28-150, VA content 28%, sourced from Beijing Dongfang Petrochemical Co., Ltd.; The photoinitiator is benzophenone; the crosslinking agent is triallyl isocyanurate; The inorganic filler is nano-silicon dioxide: fumed silica, with an average particle size of 12 nm, sourced from Degussa (China) Investment Co., Ltd.; The auxiliary agent is a mixture of antioxidant 1010 and antioxidant 300, with a mass ratio of 1:1; The ring catalyst is a cycloalkylruthenium catalyst, which is prepared by referring to 6cyc in the literature "Boydston AJ, Xia Y, Kornfield JA, et al. Cyclic ruthenium-alkylidene catalysts for ringexpansion metathesispolymerization [J]. Journal of the American Chemical Society, 2008, 130(38):12775-12782"; Sheath material: 9323, from Jiangsu Dewei New Materials Co., Ltd.; The thickness of the insulation layer and the sheath layer are both 1.5mm.
[0038] Embodiment 1: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified EVA: 1.1. Mix 15g of 2-hydroxycarbazole and triethylamine in 500mL of dichloromethane, slowly add 5-norbornene-2-yl chloride at 8°C, and add it over 20min; restore the temperature to 20°C and react for 120min; wash, let stand and separate, take the lower layer of liquid, and dry to obtain a polymerized monomer; the molar ratio of 2-hydroxycarbazole, 5-norbornene-2-yl chloride, and triethylamine is 1:1:1; Under nitrogen atmosphere, 30 g of polymerization monomer and 6.0 g of annular catalyst were mixed in 100 mL of dichloromethane, heated to 50° C., and reacted for 100 h; cooled to -20° C., and precipitated with cold methanol to obtain an alkenyl carbazole compound; 1.2. Mix 15g EVA and 300mL toluene, heat to 60℃, and stir to dissolve; slowly add 50mL 5wt% sodium hydroxide / methanol solution within 10min, and stir to react for 150min; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; 10g of EVA alcoholysis product and 1L of toluene were mixed, heated to 60°C under nitrogen atmosphere, and stirred for 60min; 2,5,5-trimethylheptanoyl chloride, 3,5,5-trimethylhexanoyl chloride and acryloyl chloride were slowly added, and the reaction was stirred for 150min; triethanolamine, an acid-binding agent, was added, and the reaction was carried out for 120min; the mixture was cooled, precipitated with ethanol, filtered, washed, and dried to obtain alkenyl EVA; the alkenyl EVA included the following mass components: 100 parts of EVA alcoholysis product, 1 part of 3,5,5-trimethylhexanoyl chloride, 3 parts of 2,5,5-trimethylheptanoyl chloride, 4.5 parts of acryloyl chloride, and 12 parts of triethanolamine, an acid-binding agent; 10g of alkenyl EVA and 100mL of toluene are mixed, dithiol compound and photoinitiator benzoin dimethyl ether are added, stirred and irradiated with ultraviolet lamp for 2h; alkenyl carbazole compound is added, and irradiation is continued for 12h; washed and dried to obtain modified EVA; the dithiol compound is 1,4-benzenedithiol; the modified EVA includes the following mass components: 100 parts of alkenyl EVA, 10 parts of alkenyl carbazole compound, 5.6 parts of dithiol compound, and 2.4 parts of photoinitiator; Step 2: Preparation of modified inorganic filler: 5 g of a cross-linking agent and 10 mL of tetrahydrofuran were mixed, and the system temperature was adjusted to 8°C under the protection of a nitrogen atmosphere. γ-mercaptopropyltrimethoxysilane and triethylamine were added, and the mixture was stirred and returned to room temperature. The mixture was kept warm for 24 hours. Allyl siloxane was obtained by distillation under reduced pressure. The molar ratio of the cross-linking agent, γ-mercaptopropyltrimethoxysilane and triethylamine was 1:1:1.8. 10g of inorganic filler was placed in 100mL of 60v% ethanol solution and ultrasonically dispersed for 20min, the pH of the system was adjusted to 3.6 with hydrochloric acid, 1g of allylsiloxane was added, the temperature was raised to 70°C, and the reaction was stirred for 12h; washed, filtered, and dried to obtain a modified filler; Step 3: Preparation of photovoltaic cables: LDPE, LLDPE, modified EVA, modified filler, photoinitiator, crosslinking agent and auxiliary agent are blended and kneaded. The kneading process conditions are as follows: temperature 145°C, rotation speed 40rmp, time 30min, to obtain an insulating material; the insulating material includes the following mass components: 80 parts of LDPE, 20 parts of LLDPE, 6 parts of modified EVA, 1 part of photoinitiator, 1 part of crosslinking agent, 0.5 parts of modified filler, and 0.2 parts of auxiliary agent; Extruding the insulating material so that the insulating material covers the conductor, the extrusion process conditions are: extrusion temperature 145°C, monomer line speed 3.0m / min; heating and irradiation to form an insulating layer, the heating process conditions are: temperature 155°C, duration 76s; irradiation process conditions are: ultraviolet lamp power 1.0W×12 groups, duration 76s; The sheath material is extruded to cover the insulating layer to form a sheath layer, thereby obtaining a photovoltaic cable.
[0039] Embodiment 2: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified EVA: 1.1. Mix 15g of 2-hydroxycarbazole and triethylamine in 500mL of dichloromethane, slowly add 5-norbornene-2-yl chloride at 4°C, and add for 20min; restore the temperature to 25°C, react for 105min; wash, let stand and separate, take the lower layer of liquid, dry, and obtain a polymerized monomer; the molar ratio of 2-hydroxycarbazole, 5-norbornene-2-yl chloride, and triethylamine is 1:1.05:1.05; Under nitrogen atmosphere, 30 g of polymerization monomer and 6.8 g of annular catalyst were mixed in 100 mL of dichloromethane, heated to 55° C., and reacted for 98 h; cooled to -20° C., and precipitated with cold methanol to obtain an alkenyl carbazole compound; 1.2. Mix 16g EVA and 300mL toluene, heat to 65°C, and stir to dissolve; slowly add 50mL 5wt% sodium hydroxide / methanol solution within 10min, and stir to react for 120min; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; 15g of EVA alcoholysis product and 1L of toluene were mixed, heated to 65°C under nitrogen atmosphere protection, and stirred for 45min; 2,5,5-trimethylheptanoyl chloride, 3,5,5-trimethylhexanoyl chloride and acryloyl chloride were slowly added, and the reaction was stirred for 135min; triethanolamine, an acid-binding agent, was added, and the reaction was carried out for 105min; the mixture was cooled, precipitated with ethanol, filtered, washed, and dried to obtain alkenyl EVA; the alkenyl EVA included the following mass components: 100 parts of EVA alcoholysis product, 2.5 parts of 3,5,5-trimethylhexanoyl chloride, 1.5 parts of 2,5,5-trimethylheptanoyl chloride, 5 parts of acryloyl chloride, and 12.5 parts of triethanolamine, an acid-binding agent; 10g of alkenyl EVA and 100mL of toluene were mixed, dithiol compound and photoinitiator benzoin dimethyl ether were added, stirred and irradiated with ultraviolet lamp for 3h; alkenyl carbazole compound was added, and irradiation was continued for 9h; washed and dried to obtain modified EVA; the dithiol compound was 1,4-benzenedithiol; the modified EVA included the following mass components: 100 parts of alkenyl EVA, 16 parts of alkenyl carbazole compound, 9.0 parts of dithiol compound, and 4.0 parts of photoinitiator; Step 2: Preparation of modified inorganic filler: 5 g of a cross-linking agent and 10 mL of tetrahydrofuran were mixed, and the system temperature was adjusted to 4°C under the protection of a nitrogen atmosphere. γ-mercaptopropyltrimethoxysilane and triethylamine were added, and the mixture was stirred and returned to room temperature. The mixture was kept warm for 25 hours. Allyl siloxane was obtained by distillation under reduced pressure. The molar ratio of the cross-linking agent, γ-mercaptopropyltrimethoxysilane and triethylamine was 1:1:2.1. 10 g of inorganic filler was placed in 100 mL of 66 v% ethanol solution and ultrasonically dispersed for 25 min. The pH of the system was adjusted to 4.0 with hydrochloric acid. 3.5 g of allylsiloxane was added. The temperature was raised to 75 ° C. and stirred for 10 h. The mixture was washed, filtered, and dried to obtain a modified filler. Step 3: Preparation of photovoltaic cables: LDPE, LLDPE, modified EVA, modified filler, photoinitiator, crosslinking agent and auxiliary agent are blended and kneaded. The kneading process conditions are as follows: temperature 150°C, rotation speed 50rmp, time 25min, to obtain an insulating material; the insulating material includes the following mass components: 80 parts of LDPE, 20 parts of LLDPE, 9 parts of modified EVA, 2 parts of photoinitiator, 2 parts of crosslinking agent, 1.5 parts of modified filler, and 0.3 parts of auxiliary agent; Extruding the insulating material so that the insulating material covers the conductor, the extrusion process conditions are: extrusion temperature 155°C, monomer line speed 3.0m / min; heating and irradiation to form an insulating layer, the heating process conditions are: temperature 160°C, duration 60; irradiation process conditions are: ultraviolet lamp power 1.0W×12 groups, duration 406s; The sheath material is extruded to cover the insulating layer to form a sheath layer, thereby obtaining a photovoltaic cable.
[0040] Embodiment 3: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified EVA: 1.1. Mix 15g of 2-hydroxycarbazole and triethylamine in 500mL of dichloromethane, slowly add 5-norbornene-2-yl chloride at 0°C, and add it over 20min; restore the temperature to 30°C and react for 90min; wash, let stand and separate, take the lower layer of liquid, and dry to obtain a polymerized monomer; the molar ratio of 2-hydroxycarbazole, 5-norbornene-2-yl chloride, and triethylamine is 1:1.1:1.1; Under nitrogen atmosphere, 30 g of polymerization monomer and 7.5 g of annular catalyst were mixed in 100 mL of dichloromethane, heated to 60° C., and reacted for 96 h; cooled to -20° C., and precipitated with cold methanol to obtain an alkenyl carbazole compound; 1.2. Mix 18g EVA and 300mL toluene, heat to 70℃, and stir to dissolve; slowly add 50mL 5wt% sodium hydroxide / methanol solution within 10min, and stir to react for 100min; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; 20g of EVA alcoholysis product and 1L of toluene were mixed, heated to 70°C under nitrogen atmosphere protection, and stirred for 30min; 3,5,5-trimethylhexanoyl chloride and acryloyl chloride were slowly added, and the reaction was stirred for 120min; triethanolamine, an acid binder, was added, and the reaction was carried out for 90min; the mixture was cooled, precipitated with ethanol, filtered, washed, and dried to obtain alkenyl EVA; the alkenyl EVA included the following mass components: 100 parts of EVA alcoholysis product, 4 parts of 3,5,5-trimethylhexanoyl chloride, 6.0 parts of acryloyl chloride, and 13 parts of triethanolamine, an acid binder; 10g of alkenyl EVA and 100mL of toluene were mixed, dithiol compound and photoinitiator benzoin dimethyl ether were added, stirred and irradiated with ultraviolet lamp for 4h; alkenyl carbazole compound was added, and irradiation was continued for 12h; washed and dried to obtain modified EVA; the dithiol compound was 1,4-benzenedithiol; the modified EVA included the following mass components: 100 parts of alkenyl EVA, 22 parts of alkenyl carbazole compound, 12.3 parts of dithiol compound, and 5.3 parts of photoinitiator; Step 2: Preparation of modified inorganic filler: 5 g of a cross-linking agent and 10 mL of tetrahydrofuran were mixed, and the system temperature was adjusted to 0°C under the protection of a nitrogen atmosphere. γ-mercaptopropyltrimethoxysilane and triethylamine were added, and the mixture was stirred and returned to room temperature. The mixture was kept warm for 27 hours. Allyl siloxane was obtained by distillation under reduced pressure. The molar ratio of the cross-linking agent, γ-mercaptopropyltrimethoxysilane and triethylamine was 1:1:2.5. 10 g of inorganic filler was placed in 100 mL of 75 v% ethanol solution and ultrasonically dispersed for 30 min. The pH of the system was adjusted to 4.2 with hydrochloric acid. 6 g of allyl siloxane was added. The temperature was raised to 80 ° C. and stirred for 8 h. The mixture was washed, filtered, and dried to obtain a modified filler. Step 3: Preparation of photovoltaic cables: LDPE, LLDPE, modified EVA, modified filler, photoinitiator, crosslinking agent and auxiliary agent are blended and kneaded. The kneading process conditions are as follows: temperature 160°C, rotation speed 60 rpm, time 20 min, to obtain an insulating material; the insulating material includes the following mass components: 80 parts of LDPE, 20 parts of LLDPE, 12 parts of modified EVA, 3 parts of photoinitiator, 3 parts of crosslinking agent, 3.0 parts of modified filler, and 0.5 parts of auxiliary agent; Extruding the insulating material so that the insulating material covers the conductor, the extrusion process conditions are: extrusion temperature 170°C, monomer line speed 3.0m / min; heating and irradiation to form an insulating layer, the heating process conditions are: temperature 170°C, duration 44s; irradiation process conditions are: ultraviolet lamp power 1.0W×12 groups, duration 76s; The sheath material is extruded to cover the insulating layer to form a sheath layer, thereby obtaining a photovoltaic cable.
[0041] Comparative Example 1: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 2: Preparation of modified inorganic filler: 10g of inorganic filler was placed in 100mL of 60v% ethanol solution and ultrasonically dispersed for 20min, the pH of the system was adjusted to 3.6 with hydrochloric acid, 1g of silane coupling agent A151 was added, the temperature was raised to 70°C, and the reaction was stirred for 12h; washed, filtered, and dried to obtain a modified filler; Step 1 and step 3 are the same as those in Example 1 to obtain a photovoltaic cable.
[0042] Comparative Example 2: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified EVA: 1.1. Under nitrogen atmosphere, 30 g of methyl 5-norbornene-2-carboxylate and 6.0 g of annular catalyst were mixed in 100 mL of dichloromethane, heated to 50 ° C, and reacted for 100 h; cooled to -20 ° C, and precipitated with cold methanol to obtain a cyclic polymer; 1.2. Mix 15g EVA and 300mL toluene, heat to 60℃, and stir to dissolve; slowly add 50mL 5wt% sodium hydroxide / methanol solution within 10min, and stir to react for 150min; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; 10g of EVA alcoholysis product and 1L of toluene were mixed, heated to 60°C under nitrogen atmosphere, and stirred for 60min; 2,5,5-trimethylheptanoyl chloride, 3,5,5-trimethylhexanoyl chloride and acryloyl chloride were slowly added, and the reaction was stirred for 150min; triethanolamine, an acid-binding agent, was added, and the reaction was carried out for 120min; the mixture was cooled, precipitated with ethanol, filtered, washed, and dried to obtain alkenyl EVA; the alkenyl EVA included the following mass components: 100 parts of EVA alcoholysis product, 1 part of 3,5,5-trimethylhexanoyl chloride, 3 parts of 2,5,5-trimethylheptanoyl chloride, 4.5 parts of acryloyl chloride, and 12 parts of triethanolamine, an acid-binding agent; 10g of alkenyl EVA and 100mL of toluene were mixed, dithiol compound and photoinitiator benzoin dimethyl ether were added, stirred and irradiated with ultraviolet lamp for 2h; cyclic polymer was added and irradiated for 12h; the modified EVA was washed and dried to obtain the dithiol compound, which was 1,4-benzenedithiol; the modified EVA included the following mass components: 100 parts of alkenyl EVA, 10 parts of cyclic polymer, 5.6 parts of dithiol compound and 2.4 parts of photoinitiator; Step 2 and step 3 are the same as those in Comparative Example 1 to obtain a photovoltaic cable.
[0043] Comparative Example 3: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified EVA: Mix 15g EVA and 300mL toluene, heat to 60°C, and stir to dissolve; slowly add 50mL 5wt% sodium hydroxide / methanol solution within 10min, and stir to react for 150min; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; 10g of EVA alcoholysis product and 1L of toluene were mixed, heated to 60°C under nitrogen atmosphere, and stirred for 60min; 2,5,5-trimethylheptanoyl chloride, 3,5,5-trimethylhexanoyl chloride and acryloyl chloride were slowly added, and the reaction was stirred for 150min; triethanolamine, an acid-binding agent, was added, and the reaction was carried out for 120min; the mixture was cooled, precipitated with ethanol, filtered, washed, and dried to obtain alkenyl EVA; the alkenyl EVA included the following mass components: 100 parts of EVA alcoholysis product, 1 part of 3,5,5-trimethylhexanoyl chloride, 3 parts of 2,5,5-trimethylheptanoyl chloride, 4.5 parts of acryloyl chloride, and 12 parts of triethanolamine, an acid-binding agent; 10g of alkenyl EVA and 100mL of toluene were mixed, dithiol compound and photoinitiator benzoin dimethyl ether were added, stirred and irradiated with ultraviolet lamp for 2h; N-vinyl carbazole was added and irradiation was continued for 12h; the modified EVA was washed and dried to obtain the dithiol compound, which was 1,4-benzenedithiol; the modified EVA included the following mass components: 100 parts of alkenyl EVA, 6 parts of N-vinyl carbazole, 5.6 parts of dithiol compound and 2.4 parts of photoinitiator; Step 2 and step 3 are the same as those in Comparative Example 1 to obtain a photovoltaic cable.
[0044] Comparative Example 4: A preparation process of a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified EVA: Mix 15g EVA and 300mL toluene, heat to 60°C, and stir to dissolve; slowly add 50mL 5wt% sodium hydroxide / methanol solution within 10min, and stir to react for 150min; cool, filter, wash and dry the precipitate to obtain EVA alcoholysis product; 10g of EVA alcoholysis product and 1L of toluene were mixed, heated to 60°C under nitrogen atmosphere protection, and stirred for 60min; 2,5,5-trimethylheptanoyl chloride and 3,5,5-trimethylhexanoyl chloride were slowly added, and the reaction was stirred for 150min; triethanolamine, an acid-binding agent, was added, and the reaction was carried out for 120min; the mixture was cooled, precipitated with ethanol, filtered, washed, and dried to obtain modified EVA; the alkenyl EVA included the following mass components: 100 parts of EVA alcoholysis product, 1 part of 3,5,5-trimethylhexanoyl chloride, 3 parts of 2,5,5-trimethylheptanoyl chloride, 4.5 parts of carbazole-9-carbonyl chloride, and 12 parts of triethanolamine, an acid-binding agent; Step 2 and step 3 are the same as those in Comparative Example 1 to obtain a photovoltaic cable.
[0045] Comparative Example 5: A preparation process for a waterproof and anti-aging photovoltaic cable, comprising the following processes: Step 1, preparation of modified filler, the same as in Comparative Example 1, to obtain modified filler; Step 2: Preparation of photovoltaic cables: LDPE, LLDPE, EVA, modified filler, photoinitiator, crosslinking agent and auxiliary agent are blended and kneaded. The kneading process conditions are as follows: temperature 145°C, rotation speed 40 rpm, time 30 min, to obtain an insulating material; the insulating material includes the following mass components: 80 parts of LDPE, 20 parts of LLDPE, 6 parts of EVA, 1 part of photoinitiator, 1 part of crosslinking agent, 0.5 parts of modified filler, and 0.2 parts of auxiliary agent; Extruding the insulating material so that the insulating material covers the conductor, the extrusion process conditions are: extrusion temperature 145°C, monomer line speed 3.0m / min; heating and irradiation to form an insulating layer, the heating process conditions are: temperature 155°C, duration 76s; irradiation process conditions are: ultraviolet lamp power 1.0W×12 groups, duration 76s; The sheath material is extruded to cover the insulating layer to form a sheath layer, thereby obtaining a photovoltaic cable.
[0046] Experiment: The photovoltaic cables obtained in Examples 1-3 and Comparative Examples 1-5 were taken to prepare samples, and their performances were tested and the test results were recorded: Mechanical properties test: GB / T 2951.11 was used as the reference standard, and an electronic universal testing machine was used to test the tensile properties of the insulating layer sample. The tensile rate was 250 mm / min, the experimental temperature was 23°C, and the sample was a type II dumbbell piece with a size of 25 mm × 4 mm × 1.0 mm. Volume resistivity test: Use a high resistance meter to detect the volume resistivity of the insulating layer sample, the test voltage is 1kV, and the sample size is Φ100mm×1.0mm; AC breakdown field strength test: Aluminum is plated on both sides of the insulating layer sample with a thickness of 100μm as electrodes, placed in silicone oil, and the voltage is increased at a rate of 4kV / s until the sample breaks down. The characteristic breakdown field strength with a failure probability of 63.2% is used as the performance data; Water resistance test: Soak the insulation layer sample in deionized water for 30 days and test its performance again; Water tree aging performance test: needles were inserted into the surface of the insulating layer sample with a sample size of 100mm×100mm×5.0mm, 30 needles, a penetration depth of 3mm, and a needle angle of 60° as the initiation and growth starting point of water tree branches. The sample was kept at 90℃ for 4h to eliminate stress. The pinhole surface was contacted with a 10wt% NaCl solution, and aluminum was plated on the other side of the insulating layer as a grounding electrode. The sample was powered on for 21d with a voltage of 4kV and a frequency of 6000Hz. The sample was taken out and stained with a 5wt% potassium permanganate solution to detect the average length of the water tree branches (along the direction of the electric field). The ratio of the number of pinholes that triggered water tree branches to the total number of pinholes was used as the probability of water tree branch growth.
[0047]
[0048] According to the data in the above table, we can clearly draw the following conclusions: The photovoltaic cables obtained in Examples 1-3 are compared with the photovoltaic cables obtained in Comparative Examples 1-5. The test results show that: Compared with the comparative example, the photovoltaic cables obtained in Examples 1-3 have better tensile strength and volume resistivity data of the insulation layer before and after immersion in water, and the average length of the water tree branches and the probability of water tree branch growth are lower. This fully demonstrates that the present invention achieves the improvement of the water resistance, water tree resistance and anti-aging performance of the insulation layer, and the photovoltaic cables prepared have better water resistance and anti-aging capabilities.
[0049] Compared with Example 1, the inorganic filler in Comparative Example 1 is obtained by surface modification of silane coupling agent A151. Compared with Comparative Example 1, the modified EVA in Comparative Example 2 is prepared from alkenyl EVA, cyclic polymer obtained by metathesis polymerization of 5-norbornene-2-carboxylic acid methyl ester and dithiol compound; the modified EVA in Comparative Example 3 is prepared from alkenyl EVA, N-vinyl carbazole and dithiol compound; the modified EVA in Comparative Example 4 is prepared from EVA alcoholysis product, 3,5,5-trimethylhexanoyl chloride and 2,5,5-trimethylheptanoyl chloride; the EVA in Comparative Example 5 is not modified. Compared with Example 1, the photovoltaic cables obtained in Comparative Examples 1-5 have lower tensile strength and volume resistivity data of the insulation layer before and after immersion in water; the average length of water dendrites and the probability of water dendrite growth increase. It can be seen that the modification process of EVA and the components used in the present invention can promote the improvement of the water resistance, water dendrite resistance and aging resistance of the insulation layer, and contribute to the improvement of the water resistance and aging resistance of photovoltaic cables.
[0050] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0051] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a waterproof and anti-aging photovoltaic cable, characterized in that: Including the following processes: LDPE, LLDPE, modified EVA, inorganic filler, photoinitiator, crosslinking agent and additives are blended and kneaded to obtain an insulating material; Extruding the insulating material so that the insulating material covers the conductor; heating and irradiating to form an insulating layer; extruding the sheath material so that the sheath material covers the insulating layer to form a sheath layer, thereby obtaining a photovoltaic cable; The modified EVA is obtained by alcoholysis of EVA and reaction with an acyl chloride compound, wherein the acyl chloride compound includes 2,5,5-trimethylheptanoyl chloride and 3,5,5-trimethylhexanoyl chloride.
2. The preparation process of a waterproof and aging-resistant photovoltaic cable according to claim 1, characterized in that: The modified EVA is prepared by the following process: Mix EVA and toluene, heat to 60-70°C, and stir to dissolve; slowly add sodium hydroxide / methanol solution within 10 minutes, stir and react for 100-150 minutes to obtain EVA alcoholysis product; The EVA alcoholysis product and toluene are mixed, heated to 60-70°C under nitrogen atmosphere, and stirred for 30-60 minutes; 2,5,5-trimethylheptanoyl chloride, 3,5,5-trimethylhexanoyl chloride and acryloyl chloride are slowly added, and stirred for reaction for 120-150 minutes; an acid binding agent is added, and the reaction is carried out for 90-120 minutes to obtain alkenyl EVA; The alkenyl EVA and toluene are mixed, a dithiol compound and a photoinitiator are added, the mixture is stirred and irradiated with an ultraviolet lamp for 2 to 4 hours; an alkenyl carbazole compound is added, and the irradiation is continued for 8 to 12 hours to obtain a modified EVA.
3. The preparation process of a waterproof and anti-aging photovoltaic cable according to claim 2, characterized in that: The alkenyl carbazole compound is prepared by the following process: Mix 2-hydroxycarbazole and triethylamine in dichloromethane, slowly add 5-norbornene-2-yl chloride at 0-8°C for 20 minutes; restore the temperature to 20-30°C, react for 90-120 minutes to obtain a polymerized monomer; Under the protection of nitrogen atmosphere, the polymerization monomer and the annular catalyst are mixed in dichloromethane, the temperature is raised to 50-60° C., and the reaction is carried out for 96-100 hours to obtain an alkenyl carbazole compound.
4. The preparation process of a waterproof and anti-aging photovoltaic cable according to claim 1, characterized in that: The inorganic filler is modified, and the specific process is as follows: Mix the crosslinking agent and tetrahydrofuran, adjust the system temperature to 0-8°C under the protection of nitrogen atmosphere, add mercaptosiloxane and triethylamine, stir and return to room temperature, keep the temperature for 24-27 hours, and distill under reduced pressure to obtain allylsiloxane; The inorganic filler is placed in an ethanol solution and ultrasonically dispersed for 20 to 30 minutes, the pH of the system is adjusted to 3.6 to 4.2 with hydrochloric acid, allyl siloxane is added, the temperature is raised to 70 to 80°C, and the reaction is stirred for 8 to 12 hours; Wash, filter and dry to obtain the modified filler.
5. The preparation process of a waterproof and anti-aging photovoltaic cable according to claim 4, characterized in that: The insulating material comprises the following components by mass: 50 to 90 parts of LDPE, 10 to 50 parts of LLDPE, 6 to 12 parts of modified EVA, 1 to 3 parts of photoinitiator, 1 to 3 parts of crosslinking agent, 0.5 to 3.0 parts of modified filler, and 0.2 to 0.5 parts of auxiliary agent.
6. The process for preparing a waterproof and anti-aging photovoltaic cable according to claim 1, characterized in that: The heating process conditions are: temperature 155-170° C., and duration 44-76 seconds.
7. The process for preparing a waterproof and anti-aging photovoltaic cable according to claim 1, characterized in that: The irradiation process conditions are: UV lamp power 1.0W×12 groups, duration 76 to 136 seconds.
8. The process for preparing a waterproof and anti-aging photovoltaic cable according to claim 2, characterized in that: The alkenyl EVA comprises the following components by mass: 100 parts of EVA alcoholysis product, 1 to 4 parts of 3,5,5-trimethylhexanoyl chloride, 0 to 3 parts of 2,5,5-trimethylheptanoyl chloride, 4.5 to 6.0 parts of acryloyl chloride, and 12 to 13 parts of an acid binding agent.
9. The process for preparing a waterproof and anti-aging photovoltaic cable according to claim 2, characterized in that: The modified EVA comprises the following components by weight: 100 parts of alkenyl EVA, 10 to 22 parts of alkenyl carbazole compounds, 5.6 to 22.1 parts of dithiol compounds, and 2.4 to 11.0 parts of photoinitiators.
10. A waterproof and anti-aging photovoltaic cable, characterized by: The invention is prepared by the preparation process described in any one of claims 1 to 9.
Citation Information
Patent Citations
Anti-migration anti-aging photovoltaic packaging adhesive film and preparation method thereof
CN116574457A
Cold-resistant electric wire and cable and preparation process thereof
CN118256032A
Organic polymers
GB8505095D0
Non-halogen flame-retardant resin composition, manufacturing method therefor, and electric cable using the same
JP2011080020A